Pemanfaatan Sarana Dan Prasarana Dinas Perpustakaan Dan Kearsipan Kabupaten Siak - Hernimawati Hernimawati; Surya Daliati; Sudaryanto Sudaryanto (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this community service is to answer the problem where the learning community has not been realized, the guidance and stimulus for library members has not run optimally, library competitions and festivals are still not optimal. The method of implementing community service is carried out by discussion, providing material explanations about the use of office facilities and infrastructure for state civil servants and the public/visitors/members of libraries and archives. As a result, the Library and Archives Office of Siak Regency has a unique and interesting building, this is adapted to the characteristics of Siak Regency in its development that adopts Arabic and European architecture. The building that was originally walled with wood and houses on stilts has now become magnificent. Various facilities and infrastructure are available for both internal and external visitors. Internally, for example, attractive bookshelves, a very comfortable adult reading room. Then from the outside of the building or externally the availability of facilities for competitions (gazebo) and a large parking area. Everything that has been built by the Siak Regency Government needs to be utilized so that it is able to educate people's lives.